Respon Aplikasi Kapur Terhadap Beberapa Sifat Kimia Tanah Lahan Pasang Surut - Akbar Paripurna; Dedik Budianta; Adipati Napoleon (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2017)
Paripurna et al, 2017. Response of Lime Application to Some Soil Chemical Properties of Tidal Swamp Land. JLSO 6(1):59-70.Tidal swamp land of Banyu Urip Village Banyuasin District South Sumatera Province has a pH 4.5, 4.96 cmolkg-1 Al-exch, >20% Al saturation, low Ca and Mg availableity and contain Pyrite. This study analyzed response of lime application to some soil chemical properties of tidal swamp land. Lime used was dolomite. The research was conducted on April 2017.Lime dosages consisted of 0.00 ton ha-1, 0.81 ton ha-1, 1.63 ton ha-1, 2.45 ton   ha-1, 3.26 ton ha-1 and 4.07 ton ha-1 respectively mixed to 10 kg soil and placed to polybags than incubated for 7 days.Variables measured were soil pH, K-exch, Ca-exch, Mg-exch, Al-exch, CEC, H-exch and Al saturation. The results showed that lime with 3.26 ton ha-1 dosage gived best results by increased Mg-exch up to 0.85 cmolkg-1 and   decreased H-exch down to 1.14 cmolkg-1, while lime with 4.07 ton ha-1 dosage gived best results by increased soil pH up to 4.95, K-exch 0.64 Cmolkg-1, Ca-exch 2.18 cmolkg-1, and CEC 15.23 cmolkg-1, also decreased Al-exch down to 1.96 cmolkg-1 and Al saturation down to 12.87%. Lime as an ameliorant to acidic soil is effective to increase soil nutrients, decrease soil acidity, Al-exch and Al saturation that influenced by fertilization.